Stabilitas Timbunan Pembangunan Infrastruktur Perumahan bagi Warga Eks Pejuang Timor – Timur dengan Menggunakan Software Geo5 dan Geostudio - Nur Ayu Diana; Reysha Rizki Amanda Lubis; Heri Budianto (Faculty of Engineering, Widya Kartika University, 2026)
Embankmentswere constructed to increase land elevation, necessitating an evaluation of landslide potential. The analysis was conducted using the limit equilibrium method using the Morgenstern-Price method. Soil parameters were obtained from laboratory testing, including compaction tests (Standard Proctor), California Bearing Ratio (CBR) tests, and gradation analysis. These were then supplemented with empirical correlations to determine cohesion and angle of internal friction. Modeling was performed using GEO5 and GeoStudio software (SLOPE/W), considering the original soil layer, embankment soil, and a stabilization layer using additives. The analysis results showed a factor of safety of 58.30 (GEO5) and 69.74 (GeoStudio), both of which are greater than the minimum required value (SF > 1.5). This indicates that the embankment is very stable and safe from potential landslides. This study confirms that the use of stabilization materials can significantly increase soil strength and support safe and reliable construction planning.